Aortic dissection: case series - Rao, Bhavana Venkata Nagabhushana (International Journal of Research in Medical Sciences, 2016)
Aortic dissection may not be attended by a physician in his lifetime, but he should possess all the clinical acumen to deal with as it is a catastrophic disease. Early and accurate diagnosis will save a life. Here we present three cases we faced in sequence over a period of two months. A case of extensive dissection arch to thoracic aorta, its display in detail. Second case eliciting ambiguity between coronary ischemia and aortic dissection. Management difficulties of such clinician situation are discussed. Third case, the fracture of a renal artery stent leading to severe hypertension, abdominal pain, and aortic dissection. Such case was not described in the literature to our knowledge.